OPTIMALISASI REKONFIGURASI PEMBANGKIT LISTRIK TENAGA GAS DAN UAP TAMBAK LOROK SEMARANG - Agus Adhi Nugroho; Muhammad Haddin; Muhammad Alief Rizky Kurniawan (Universitas Muhammadiyah Semarang, 2018)
The Reliability and the quality of electric energy is not enough to make a consideration in deciding which power plant is choose in the utility business. Some of the power plant operated in Central Java still using power plant that has expensive generating cost, especially steam and gas power plant (PLTGU). In order to make economically viable, there must be calculation on generating cost and make some optimization through reconfiguration of power plant using Digsilent simulator. Filled with conductors capacity, power plant capacity, and the load, Digsilent will calculate the load simulation. When PLTGU block 2 not operated, so IBT 500/150 kV Ungaran 1 and 2 suffer overload for 103%, causing voltage drop to 134 kV. After some reconfiguration simulation, the load in IBT 500/150 kV Ungaran 1 and 2 drop to 76%, while the voltage maintain to 140 kV. Decreasing the production cost as much as Rp.107.600.400.000,- in a month. Keywords: PLTGU, Optimization, Digsilent, production cost